Catalytic pyrolysis of rain tree biomass with nano nickel oxide synthetized from nickel plating slag: a green path for treating waste by waste - Guo, Dabin (2022)
Catalytic pyrolysis of rain tree biomass (RTB), a typical horticultural waste, was investigated with nano-NiO as catalyst produced from hazardous nickel plating slag (NPS). It appeared from the analyses by FTIR, TGA, XRD, BET, and FESEM/EDX that nano-NiO produced had a SBET and mean particle size of 53.4 m2/g and 112.3 nm. The catalytic pyrolysis kinetics of RTB with and without catalyst were studied by Friedman method. It was found that the activation energy (Ea) was in the range of 177 to 360 kJ/mol at a conversion rate of 0.1 - 0.75. The results further revealed that the H2 increase ratio in pyrolysis above 500 °C was more than 40% in the presence of catalyst. Consequently, this study showed the great potential of nano-NiO as a high-efficiency catalyst in recovering energy from biomass.